Shear Behavior of Granulated Blast Furnace Slag-Based Geopolymer-Reinforced Concrete Beams - Ozturk, Mehdi; Arslan, Guray (MDPI, 2022)
Active research is ongoing regarding the mechanical behavior of structural members manufactured from geopolymer concrete (GC), as it lacks standardized/codified manufacturing and design procedures. This study aims to address the shear behavior of GC beams. First, a consistent trial-error-based approach was used to develop the optimal mixture ratio (102.38/234.0 for NaOH/Na2SiO3) in terms of workability and consistency for the production of six (6) test specimens with span-to-depth ratios of (a/d) of 2.5, 3.5, and 4.5 and transverse reinforcement intervals of 10, 15, and 20 cm. Then, shear failure tests using a three-point bending setup were conducted and analyzed statistically. As a first attempt in the literature, an empirical expression for shear capacity prediction that was specifically tuned for GC beams was given. This expression, along with seven other similar expressions for ordinary concrete beams from the literature, and various practice codes were tested against a pool of experimental shear failure results given by four (4) different researchers. As a measure of the predictive capability, coefficient of variation (COV = standard deviation/average) values were obtained, and the lowest COV value of 0.305 suggested that the expression obtained the highest predictive capability, whereas more common practice codes such as ACI318, EN1992, and ENV1992 produced COV values of 0.435, 0.374, and 0.627, respectively. Finally, this study provides a working expression for the shear capacity estimation of GC beams and a mixture ratio for the practical manufacturing conditions of workability and consistency, with a slump value of 270 mm and a 90 min setting time.
Keywords: geopolymer concrete; shear; beam; sustainable materials; STRENGTH MODEL; PERFORMANCE; Construction & Building Technology; Engineering